2020
DOI: 10.1186/s40900-020-00229-y
|View full text |Cite
|
Sign up to set email alerts
|

‘All hands-on deck’, working together to develop UK standards for public involvement in research

Abstract: Background Public involvement in research is an established part of the research process in the UK, however there remain questions about what good public involvement in research looks and feels like. Until now public involvement practitioners, researchers and members of the public have looked for answers in examples shared across networks, published case studies, guidance and research articles. Pulling these strands together, the UK Standards for Public Involvement provides six statements (standards) about pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…However, in DC2 one group leader reported that everybody had viewpoints on the illustrations and that Nora and Helmer contributed to opening discussions. Overall, the experience of the project group, in line with Crowe et al [ 47 ], was that using the illustrations of Nora and Helmer facilitated reflections and mutual learning between researchers and participants.…”
Section: Discussionmentioning
confidence: 60%
“…However, in DC2 one group leader reported that everybody had viewpoints on the illustrations and that Nora and Helmer contributed to opening discussions. Overall, the experience of the project group, in line with Crowe et al [ 47 ], was that using the illustrations of Nora and Helmer facilitated reflections and mutual learning between researchers and participants.…”
Section: Discussionmentioning
confidence: 60%
“…We used the UK Standards for Public Involvement [20] to guide our work with the public, and in reporting this project, we use the GRIPP 2 checklist [21] so that the specific elements of public involvement are described and evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…We recruited two more service users to the Trial Steering Committee through Involving People (http://www.wales.nhs.uk/sites3/page.cfm?orgid=1023&pid=59261) to ensure their independence. We followed best practice by ensuring all users received honoraria, expenses, training and support, a named contact, information and networking opportunities [42].…”
Section: Methodsmentioning
confidence: 99%